Darunavir Nanoformulation Suppresses HIV Pathogenesis in Macrophages and Improves Drug Delivery to the Brain in Mice - Lina Zhou; Sandip Godse; Namita Sinha; Sunitha Kodidela; Udai Singh; Santosh Kumar (MDPI AG, 2024)
Although antiretroviral therapy (ART) can suppress peripheral HIV, patients still suffer from neuroHIV due to insufficient levels of ART drugs in the brain. Hence, this study focuses on developing a poly lactic-co-glycolic acid (PLGA) nanoparticle-based ART drug delivery system for darunavir (DRV) using an intranasal route that can overcome the limitation of drug metabolic stability and blood-brain barrier (BBB) permeability. The physicochemical properties of PLGA-DRV were characterized. The results indicated that PLGA-DRV formulation inhibits HIV replication in U1 macrophages directly and in the presence of the BBB without inducing cytotoxicity. However, the PLGA-DRV did not inhibit HIV replication more than DRV alone. Notably, the total antioxidant capacity remained unchanged upon treatment with both DRV or PLGA-DRV in U1 cells. Compared to DRV alone, PLGA-DRV further decreased reactive oxygen species, suggesting a decrease in oxidative stress by the formulation. Oxidative stress is generally increased by HIV infection, leading to increased inflammation. Although the PLGA-DRV formulation did not further reduce the inflammatory response, the formulation did not provoke an inflammatory response in HIV-infected U1 macrophages. As expected, in vitro experiments showed higher DRV permeability by PLGA-DRV than DRV alone to U1 macrophages. Importantly, in vivo experiments, especially using intranasal administration of PLGA-DRV in wild-type mice, demonstrated a significant increase in the brain-to-plasma ratio of DRV compared to the free DRV. Overall, findings from this study attest to the potential of the PLGA-DRV nanoformulation in reducing HIV pathogenesis in macrophages and enhancing drug delivery to the brain, offering a promising avenue for treating HIV-related neurological disorders.